Efektifitas Model Pembelajaran Ekspositori terhadap Hasil Belajar Peserta Didik - Fatya Dewi Mayada; Fransiska Faizah; Kamilia Nisa’i (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2024)
Strategy is an effort to achieve success and success in achieving goals. In the world of education, strategy can be interpreted as a plan that contains a series of activities designed to achieve certain learning goals. The selection of learning strategies is carried out by considering the situation and conditions, learning resources, needs and characteristics of the students faced. The strategies used by teachers greatly influence student learning outcomes. This research was conducted on 19 students, the type of research used was experimental research with a One Group Pretest-Posttest Design by giving pre-tests and post-tests to students. The aim of this research is to determine the effectiveness of the expository learning model using the N-Gain improvement test. The results of research using data calculations using Microsoft Excel show that the pre-test learning outcome is 3.3 and the post-test is 5 and the N-Gain is 1 and the N-Gain percentage value is 100%, which means that the expository learning model is effective in achieving objectives as proven by the results. the percentage of N-Gain that is included in the effective category.